Renal Doppler Indices in Children with Nephrotic Syndrome: Findings from a Tertiary Hospital in Nigeria (Nigerian Journal of Physiological Sciences, 2021)
Summary: The resistive and pulsatility indices are known tools for assessing renal function in kidney diseases, especially in proteinuric conditions like Paediatric Nephrotic syndrome (NS) which is a glomerular disease. However, there is a limited knowledge in the use of Doppler Resistive and pulsatility indices in the management of this disease condition. This was a case control study involving 53 cases and 57 controls. The Doppler parameters, resistive index (RI) and pulsatility index (PI) of the renal interlobar arteries were determined for the upper, middle, and lower poles bilaterally for both controls and cases. The mean RI on the right and left were 0.59 ± 0.06 and 0.58 ± 0.06 respectively for the NS cases whereas for the controls it was 0.61 ± 0.05 and 0.60 ± 0.04 on the right and left respectively. The mean PI on the right and left measured 0.96 ± 0.16 and 0.94 ± 0.15 respectively for the NS cases while that for the control cases measured 0.98 ± 0.13.and 0.95 ± 0.12 on the right and left respectively. Although, the interlobar arteries mean RIs were generally less than that for the controls, but only the left middle pole showed statistically significant mean difference (p= 0.004). There was also statistically significant mean difference (p= 0.048) between the cases and controls in the left middle pole PI. However, no correlation was found when the renal RI and PI are compared with the serum albumin and creatinine. Although there was no statistical significance between the mean RI and PI of the NS cases and controls, except in the left middle pole RI, it is recommended that Doppler ultrasound should still be part of management of Nephrotic syndrome patients especially those who have developed end stage renal disease in order to monitor their renal function.